Behaviour and sun exposure in holidaymakers alters skin microbiota composition and diversity - Willmott, Thomas; Campbell, Paul M.; Griffiths, Christopher E. M.; O’Connor, Clare; Bell, Michael; Watson, Rachel E. B.; McBain, Andrew J.; Langton, Abigail K. (Frontiers in Aging, 2023)
The skin microbiota plays a crucial role in maintaining epidermal homeostasis. Ultraviolet radiation (UVR) and other environmental challenges can impact the skin microbiota through direct and indirect mechanisms. This study aimed to investigate the effects of sun exposure on the skin microbiota and its relationship with individual skin phototypes.Methods: Healthy volunteers (n=21 [4M, 17F], mean age 33.2 years) holidayed in a sunny destination for a minimum of seven days with swabs taken pre-holiday and up to 84 days postholiday. Participant group was categorised by individual typology angle (ITA) classification and the composition of the skin microbiota was examined using 16S rRNA gene sequencing.Results: In the entire cohort and at all time points, the major bacterial phyla were Actinobacteria, Proteobacteria and Firmicutes. There was a significant change in microbial beta diversity at day 28 post-holiday, compared to baseline, for all participants. However, when participants were segregated into three cohorts dependent on the degree of skin tanning response between baseline (pre-holiday) and immediately one-day post-holiday, there was a reduction in Proteobacteria in the sun-seeking participants one day after the holiday, which recovered over time.Discussion: These findings suggest that sun exposure can affect the diversity and composition of the skin microbiota, which may have downstream effects on skin health.